Use of Near Infrared Spectroscopy to Asses Remote Ischemic Preconditioning in Skeletal Muscle. (21st February 2013) - Ambrozic, Jana; Lainscak, Mitja; Podbregar, Matej
Abstract : Remote ischemic preconditioning (IPC) is a procedure during which brief periods of ischemia protect distant organ from ischemia-reperfusion injury. Appling IPC on an upper arm, this phenomenon has been demonstrated in several studies. Skeletal muscle tissue oxygenation at rest (StO2 ) and StO2 deoxygenation rate during vascular occlusion can be measured using near infrared spectroscopy (NIRS). We aimed to investigate the effects of remote upper arm IPC on StO2 and flow-mediated dilatation (FMD) in healthy male volunteers. In a randomized controlled crossover trial, resting StO2, StO2 deoxygenation rate, and FMD were measured on testing arm at baseline and after 60 minutes. After basal measurements IPC protocol on a contralateral arm was performed. StO2 deoxygenation rate was significantly lower after remote, the IPC cycles in comparison to deoxygenation rate at baseline (9.7 ± 2.6 versus 7.5 ± 2.5 %, P = 0.002 ). Comparison of deoxygenation rates showed a significant difference between the IPC and the control protocol (F = 5.512, P = 0.003 ). No differences were observed in FMD before and after remote IPC and in the control protocol. In healthy young adults, remote IPC reduces StO2 deoxygenation rate but has no significant impact on FMD. NIRS technique offers a novel approach to asses skeletal muscle adaptation in response to remote ischemic stimuli.